Comprehensive review of the resistance mechanisms of colorectal cancer classified by therapy type - Oh, Janice M.; Kim, Susan; Tsung, Carolyn; Kent, Eric; Jain, Arad; Ruff, Samantha M.; Zhang, Hongji (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is the fourth most diagnosed cancer and the second leading cause of cancer-related death in the United States. Despite advancements in treatment—including chemotherapy, targeted therapy with epidermal growth factor receptor antibodies, and immunotherapy with immune checkpoint inhibitors—many CRC cases exhibit intrinsic or acquired resistance to cancer treatment, leading to limited treatment efficacy and high recurrence rates. Resistance mechanisms encompass evasion of cell death pathways, alterations in drug metabolism, modulations of the tumor microenvironment, dysregulation of signaling pathways, and metabolic reprogramming. This review aims to provide a comprehensive overview of CRC resistance mechanisms categorized by therapy type, and to discuss emerging strategies, such as nanotechnology-based approaches, to address these therapeutic challenges.